Mental Health and Minority Status: A Reading of William Faulkner’s "A Rose for Family" (Mwanga wa Lugha, 2023)
This paper undertakes a postmodernist reading of William Faulkner’s ‘A Rose for Emily’. It imbibes the binary notion of order versus chaos to interrogate the seeming madness of the main character in the story. The aim is to demonstrate how Emily, being a minority in her community, battles with mental or psychological challenges, which are products of her environment. The study relies on a close reading of the short story, and deploys postmodernism as a theoretical basis. In this paper, we argue that, the main character, Emily represents the minority in society. She is mentally unhinged (mad) because of the tragedies she has gone through. She is also a social recluse. Besides, she is a woman. To top it all, she is a criminal, a murderer. Faulkner thus uses Emily to give voice to the socially awkward or eccentric individuals. As we read the story, we begin to see that her madness is not random. It is a product of a larger society that has gone rogue. Emily is a product of the maltreatment and segregation she has suffered from a society that refuses to accept her. She embodies well Francis Imbuga’s (1987) statement: “When the madness of an entire nation disturbs a solitary mind, it is not enough to say that the man [or woman] is mad.”